Endoscopic Transmural Necrosectomy: Timing, Indications, and Methods - Rungsun Rerknimitr (Clinical Endoscopy, 2020)
Walled-off necrosis is considered one of the most severe complications after an episode of severe acute pancreatitis. Traditionally, percutaneous drainage is selected as the first treatment step, while open surgery can be planned as a secondary option if necrosectomy is required. In recent years, endoscopic necrosectomy has evolved as a more favorable approach. To date, a step-up treatment strategy is recommended, particularly when a plastic stent is selected as the drainage device. Multi-gateway endoscopic therapy may be used in a step-up fashion if only one stent fails to clear debris. Over many years, there has been an evolution in stent selection, from plastic to metallic stents. Within a few years of its clinical usage, lumen-apposing stents are gaining more popularity as they offer direct endoscopic necrosectomy and only require a few sessions.